2020
DOI: 10.3389/fnhum.2020.00218
|View full text |Cite
|
Sign up to set email alerts
|

How Much Do Strategy Reports Tell About the Outcomes of Neurofeedback Training? A Study on the Voluntary Up-Regulation of the Sensorimotor Rhythm

Abstract: The core learning mechanisms of neurofeedback (NF) training are associative, implicit, and, consequently, largely impervious to consciousness. Many other aspects of training that determine training outcomes, however, are accessible to conscious processing. The outcomes of sensorimotor rhythm (SMR) up-regulation training are related to the strategies reported by participants. The classification methods of individual strategies employed hitherto were possibly under influence of the idiosyncratic interpretation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 31 publications
2
45
5
Order By: Relevance
“…Before and after the 10 NF training sessions, resting EEG measurements with open eyes with a duration of 1 min each were performed. After the first, fifth, and tenth NF training session, we asked the participants to verbally describe their mental strategies, which they have used to control the feedback bars (Kober et al, 2013(Kober et al, , 2017cDavelaar et al, 2018;Autenrieth et al, 2020).…”
Section: Procedures and Pre-post Assessment Of Cognitive Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before and after the 10 NF training sessions, resting EEG measurements with open eyes with a duration of 1 min each were performed. After the first, fifth, and tenth NF training session, we asked the participants to verbally describe their mental strategies, which they have used to control the feedback bars (Kober et al, 2013(Kober et al, , 2017cDavelaar et al, 2018;Autenrieth et al, 2020).…”
Section: Procedures and Pre-post Assessment Of Cognitive Functionmentioning
confidence: 99%
“…These reports were analyzed descriptively to reveal possible relationships between the used mental strategies and the ability to up-/down-regulate SMR coherence. Prior amplitude-based NF studies showed that the used mental strategy might be informative for the NF training success (Nan et al, 2012;Kober et al, 2013Kober et al, , 2017cAutenrieth et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, imagining a gesture would activate corresponding pre-motor areas, pleasant autobiographic memories can affect PFC asymmetry, concentrating on your inner self may activate the insula (Lawrence et al, 2014), and achieving a relaxed state may decrease the amygdala activity. Cognitive strategies may be suggested by the experimenter, or may be discovered by the subjects themselves based on the (often partial) experimental brief they have been given (Autenrieth et al, 2020). Some of the cognitive strategies may actually lack specificity: for PFC asymmetry in which valence and approach may be confounded, the use of positive autobiographic memories as a cognitive strategy may actually bias activation from a valence perspective.…”
Section: Neurofeedback Conceptsmentioning
confidence: 99%
“…In terms of experimental protocol and validation, clinical NF tends to rely on sham feedback as a control group, under the hypothesis that appropriate feedback provides the reward signal that mediates long-term effects. The clinical context implies and allows the use of repeated sessions with significant training, which increases the number of responders: on the other hand, BCI NF dedicates limited time to subjects training and leaves non-responders to the various categories of BCI illiteracy (Lee et al, 2014;Trambaiolli et al, 2018;Autenrieth et al, 2020), concentrating instead on the responders' behavior.…”
Section: Common Description Of Fnirs Nf Experimentsmentioning
confidence: 99%
See 1 more Smart Citation